Vegetation dynamics in the Madiwatershed, Gandaki Province of Nepal (Geographical Journal of Nepal, 2023)
Monitoring of Spatio-temporal vegetation dynamic is one of the most important indicators used to track environmental quality. Spatial and temporal dynamics of Normalized Difference Vegetation Index (NDVI) values are the most useful and reliable technique to analyze the general vegetation dynamics at the regional level. Thus, this study analyzed the spatial pattern and temporal trend of NDVI values of naturally vegetated areas in the Madi Watershed of Nepal relating to its geomorphic and built-up density factors in 2000, 2010,and 2020. Lands at images were used to derive NDVI values and SRTM DEM and the topographic map were used to derive geomorphic factors and built-up density. This study excluded cultivated land, built-up area, water body, cliff, snow-cover area, glacier, and glacier moraine areas to derive only naturally vegetated areas. Human population data was collected from the population censuses. Field observation and information collected from the field to verify ground reality in 15 different watersheds. This study revealed that there is a significant increase in natural vegetation in all parts of the watershed. However, there is the highest rate of increase in vegetation in lower plain areas, where the population density is the highest. The overall increase in natural vegetation is because of the decreasing human and livestock population, changes in lifestyle, etc. The highest increase in natural vegetation in lower plain areas is because of the alternative use of cooking energy and building materials in urban and accessible areas, decreasing the number of livestock. Thus, it can be concluded that there is a significant impact of population dynamics on vegetation in the Madi Watershed of Nepal.